Effect of propeller wash on sediment transport - Ang, Xiu Xuan (2012)
Modern large ship vessels are equipped with strong side-thrusters to secure fast navigational speed and manoeuvrability. A direct consequence of the vessel size and associated larger draft is an increase in interaction between the vessel and the seabed, inducing scour and causing severe damage to the bed and nearby structures such as quay walls. In this study, an experimental investigation of the effect of a propeller on sediment transport is discussed. In the five runs conducted, variables such as the height of the propeller from the test bed, the rotational speed of the propeller and the diameter of the propeller are changed. Experimental results show that the equilibrium scour profile comprises of three components, which is a small scour hole directly beneath the propeller; a primary scour hole downstream of the small scour hole; and a sand dune farther downstream of the primary scour hole. Velocity measurements were also performed using an Acoustic Doppler Velocity Profiler. It was found that the horizontal velocity component decays at different rates in the zone of flow establishment (ZFE) and the zone of established flow (ZEF). A phenomenon whereby velocity profiles of the propeller jet showed deviation from Hamill (1987)’s velocity equation was also observed for distances farther away from the propeller, whereby velocity profiles appeared to be larger in magnitude at areas nearer to the test bed as compared to areas above the centreline of the propeller. This can be explained using the concept of boundary effect of the propeller jet, whereby the velocity wash is reflected at the bottom before merging with the original velocity wash at the bottom half of the velocity profile.